GAMBARAN TINGKAT DEPRESI BERDASARKAN TEMPAT TINGGAL PADA MAHASISWA TINGKAT PERTAMA KAMPUS SOBO PSDKU UNIVERSITAS AIRLANGGA DI BANYUWANGI: Representation Of Freshmen's Depression Levels Based On Residency Of Sobo Campus PSDKU Universitas Airlangga Banyuwangi - Evi Lutfiani Khoiriyah; Desak Made Sintha Dewi (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2019)
The prevalence of people suffering from depression in Indonesia is 21,8 percent. The percentage shows that there is a 12,1 percent higher prevalence compared to the global prevalence. Depression can affect anyone, including the freshman year students who are undergoing a transition of the development phase from secondary education to college education as late teenagers. The transition causes conflicts and adjustments as there is a culture shock that may trigger the depression. Depression is a mental disorder marked by the appearance of symptoms such as the loss of interest, feelings of guilt, mood loss, sleep disorder, and eating disorders. Thus, this research aims at figuring out the picture of depression levels based on residency among freshman year students in Sobo campus PSDKU Universitas Airlangga in Banyuwangi. This research is descriptive quantitative research using a cross-sectional study conducted on May 16, 2019, to May 20, 2019, with a total population of 83 students. The data mining technique used in this research is done by spreading the questionnaire of The Zung Self Depression Scale. The previously processed data through cleaning, coding, and tabulation stages are presented in table and description. The result showed Freshman year students who live by themselves or in boarding houses are included in the category of normal depression level with the most number of 60 people (72,29%). Meanwhile, freshmen year students who live with other people are included in the same category with less number of 8 people (9,64%). The conclusion of this reseach, depression level experienced by freshman year students of Sobo campus PSDKU Universitas Airlangga in Banyuwangi tends to be in the category of normal depression, which can be handled well to prevent the change from normal depression to mild or severe depression. The students can practice their adaptation skills and do coping according to their self-states, for instance doing physical activities.